Sonication-induced scission of molecular bottlebrushes: Implications of the "hairy" architecture. (10th February 2016) - Li, Yuanchao; Niu, Zhenbin; Burdyńska, Joanna; Nese, Alper; Zhou, Yang; Kean, Zachary S.; Dobrynin, Andrey V.; Matyjaszewski, Krzysztof; Craig, Stephen L.; Sheiko, Sergei S.
Abstract: Polymer bottlebrushes may be viewed as hairy flexible cylinders with a long backbone and a thick corona of densely grafted polymer chains. The corona not only controls the bottlebrush diameter, but also provides an additional drag force. We report the study of backbone scission by external forces caused by ultrasonication. A series of bottlebrushes with the same backbone and different side-chain lengths was prepared by ATRP. Bond fracture was induced by pulsed ultrasound in a dilute chloroform solution and ex-situ monitored through molecular imaging of reaction products by atomic force microscopy. The scission rate was found to increase with side chain length, while the limiting length of fractured bottlebrushes displayed a decrease. The experiment showed a good agreement with the Rouse model of polymer dynamics, which suggests that solvent drains through the corona of bottlebrush side-chains. Graphical abstract: Highlights: First observation of bond scission in molecular bottlebrushes upon sonication. Higher scission rates and smaller products of "hairy" macromolecules. A stronger drag force is consistent with the Rouse dynamics.